2015
DOI: 10.1097/coh.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

How does the timing of antiretroviral therapy initiation in acute infection affect HIV reservoirs?

Abstract: Purpose of review The long-lived viral reservoir is a major obstacle to achieving a cure for HIV. Therapeutic strategies, such as early antiretroviral therapy (ART), may be a prerequisite to achieving long-term control of viral replication upon ART withdrawal. Recent findings HIV persistence is established early in acute HIV infection (AHI) with infection in long-lived memory CD4+ T cells. Studies conducted in nonhuman primates have suggested that this could occur as early as 3 days postinfection; however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 40 publications
4
94
0
Order By: Relevance
“…4,5,21,22 Patients treated during acute infection are also ideal candidates for curative interventions as early therapy prevents immune damage and limits seeding of reservoirs. 23,24 According to the 2012 Human Science Research Council South African National HIV Prevalence, Incidence and Behaviour Survey, the overall HIV incidence in 2 -49-year-old individuals was 1.07%. However, as the epidemic is generalised, it is difficult to define risk groups, apart from a higher incidence among young black female survey participants.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,21,22 Patients treated during acute infection are also ideal candidates for curative interventions as early therapy prevents immune damage and limits seeding of reservoirs. 23,24 According to the 2012 Human Science Research Council South African National HIV Prevalence, Incidence and Behaviour Survey, the overall HIV incidence in 2 -49-year-old individuals was 1.07%. However, as the epidemic is generalised, it is difficult to define risk groups, apart from a higher incidence among young black female survey participants.…”
Section: Discussionmentioning
confidence: 99%
“…21,32,37,40 Duration of ART at PHI Three randomised controlled trials in PHI reported a modest benefit (delaying the decline in CD4 cell count, or time from PHI, to requiring lifelong ART) following a 48-week 38 or 60-week 39,40 course of ART. Interruption of therapy even if started close to the time of PHI is no longer recommended.…”
Section: 36mentioning
confidence: 99%
“…[24][25][26] > Reduction in the enhanced risk of onward transmission of HIV associated with PHI. [27][28][29][30][31][32] > Limitation in the size of latent pool of HIV-infected cells; the viral reservoir, 33,35 which has been associated with risk of missed diagnoses of acute HIV infection, the presence of certain indicator diseases should trigger the offer of HIV testing, 16,17 for individuals presenting with signs or symptoms of Epstein-Barr virus, cytomegalovirus, secondary syphilis, tuberculosis and bacterial pneumonia. As a result of the challenges with current technology at accurately diagnosing acute HIV infection, encouraging both access and increasing the frequency of HIV testing among those at highest risk are key to improving timely identification of PHI.…”
Section: > Preservation Of Cd4 T Lymphocytes (Total Cd4 Counts Andmentioning
confidence: 99%
“…17 On an individual patient basis, those demonstrating the greatest benefit from immunotherapy (with improved clinical and immunological parameters) received cART at earlier stages following infection, which concurs with a number of reports. 18,19 There is an emerging consensus that early initiation of cART is an essential aspect of long-term control of HIV-1 and likely to be critical in future latency reversal approaches. 19 …”
Section: Early Initiation Of Cart Facilitates Efficacious Immunotheramentioning
confidence: 99%
“…18,19 There is an emerging consensus that early initiation of cART is an essential aspect of long-term control of HIV-1 and likely to be critical in future latency reversal approaches. 19 …”
Section: Early Initiation Of Cart Facilitates Efficacious Immunotheramentioning
confidence: 99%